Which Biological Properties of Heart Valves Are Relevant to Tissue Engineering? - Chester, Adrian H.; Grande-Allen, K. Jane (Frontiers in Cardiovascular Medicine, 2020)
Over the last 20 years, the designs of tissue engineered heart valves have evolved considerably. An initial focus on replicating the mechanical and structural features of semilunar valves has expanded to endeavors to mimic the biological behavior of heart valve cells as well. Studies on the biology of heart valves have shown that the function and durability of native valves is underpinned by complex interactions between the valve cells, the extracellular matrix and the mechanical environment in which heart valves function. The ability of valve interstitial cells to synthesize extracellular matrix proteins and remodeling enzymes and the protective mediators released by endothelial cells are key factors in the homeostasis of valve function. The extracellular matrix provides the mechanical strength and flexibility required for the valve to function, as well as communicating with the cells that are bound within. There are a number of regulatory mechanisms that influence valve function, which include neuronal mechanisms and the tight regulation of growth and angiogenic factors. Together, studies into valve biology have provided a blueprint for what a tissue engineered valve would need to be capable of, in order to truly match the function of the native valve. This review addresses the biological functions of heart valve cells, in addition to the influence of the cells’ environment on this behavior and examines how well these functions are addressed within the current strategies for tissue engineering heart valves in vitro, in vivo, and in situ.